Odpowiedzi

Najlepsza Odpowiedź!
2010-01-11T21:11:04+01:00
X-pierwsza liczba
y-druga liczba

x/y=3/2
x-6=3(y-6)

3y=2x
x-6=3y-18

3y-2x=0
x-3y=-12 |*2

3y-2x=0
2x-6y=-24
------------
-3y=-24
y=8
x=12
1 5 1
  • Użytkownik Zadane
2010-01-11T21:11:22+01:00
X- pierwsza liczba
y- druga liczba

x/y = 3/2
2x = 3y

x-6 = 3(y-6)
x-6 = 3y-18
x-6 = 2x-18
-x = -12
x = 12

2x = 2y
2×12 = 2y
24 = 3y
y = 8

x=12
y=8
2010-01-11T21:14:04+01:00
X-pewna liczba
3x-pierwsza szukana liczba
2x-druga szukana
3x-6- pierwssza liczba po odjęciu 6
2x-6- druga liczba po odjęciu 6
3x-6=3(2x-6)
3x-6=6x-18
3x-6x=-18+6
-3x=-12/-3
x=4

3*4=12
2*4=8